1990
DOI: 10.1007/bf00190418
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating fluid forces acting on a circular cylinder and interference with a plane wall

Abstract: The flow around a circular cylinder placed close to a horizontal plane wall was investigated experimentally. Fluctuations of lift and drag of the cylinder and wall interference effects were studied in terms of the gap height between the cylinder and wall and the thickness of the turbulent wall boundary layer. The fluctuating fluid forces acting on the cylinder sharply increased, and the regular vortex shedding, i.e. Kfirman vortex streets, started to form beyond a critical gap height. The formation of Kfirman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
5
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(62 citation statements)
references
References 12 publications
4
52
5
1
Order By: Relevance
“…Moreover, the PIV results [ Figure 7(c, d)] indicate that the inner shear-layer remains &&frozen'' for a considerable period of time and, unlike the outer shear-layer, does not roll up. It should be noted that, contrary to the suggestions of Grass et al (1984) and Taniguchi & Miyakoshi (1990), the two shear-layers associated with the wall and the inside of the cylinder, although of di!erent sign vorticity, do not cancel each other out. A spectral analysis of the wake for G/D"0)25 revealed that, in common with the results for &&very small gap ratios'', St of the dominant wake periodicity is very dependent on Re, see Figure 8(a).…”
Section: Small Gap Ratios (G/d"0)25 and 0)375)contrasting
confidence: 52%
See 2 more Smart Citations
“…Moreover, the PIV results [ Figure 7(c, d)] indicate that the inner shear-layer remains &&frozen'' for a considerable period of time and, unlike the outer shear-layer, does not roll up. It should be noted that, contrary to the suggestions of Grass et al (1984) and Taniguchi & Miyakoshi (1990), the two shear-layers associated with the wall and the inside of the cylinder, although of di!erent sign vorticity, do not cancel each other out. A spectral analysis of the wake for G/D"0)25 revealed that, in common with the results for &&very small gap ratios'', St of the dominant wake periodicity is very dependent on Re, see Figure 8(a).…”
Section: Small Gap Ratios (G/d"0)25 and 0)375)contrasting
confidence: 52%
“…Hence, it appears that the variation of St with G/D is very dependent on the Reynolds number, and that the Strouhal number is much more sensitive to G/D in the low Reynolds number range of the present experiments. Buresti & Lanciotti (1979), Taniguchi & Miyakoshi (1990) and Lei et al (1999), 1)3;104Re41)4;10, 0)14 /D41)64.…”
Section: Small Gap Ratios (G/d"0)25 and 0)375)mentioning
confidence: 99%
See 1 more Smart Citation
“…It might still be possible to argue that the very thin boundary layer locally developed on the moving ground generates vorticity of opposite sign and thus to interfere with the separated shear layer from the bottom side of the cylinder, just like the cases with a thick boundary layer formed on a fixed ground. 8,24 Judging from the mean spanwise vorticity contours ͓cf. Figs.…”
Section: -7mentioning
confidence: 99%
“…Studies can also be found that investigate flows around cylinders in the vicinity of a wall (e.g, Brown 1967, Grace 1971, Yamamoto et al 1974, Sarpkaya and Rajabi 1979, Knoll and Herbich 1980, Freds0e and Hansen 1987, Taniguchi and Miyakoshi 1990, Sumer et al 1991. The investigations consider steady and unsteady flow forces acting on restrained cylinders frequently with a small gap between the cylinder and the wall.…”
Section: Background*mentioning
confidence: 99%